Pengaruh Evaluasi Kinerja dan Motivasi Kerja Karyawan terhadap Kualitas Pelayanan Frontliner - Khairani, Nazla; Nasution, Juliana (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to determine the effect of performance evaluation and employee motivation on frontliner service quality at Bank Btn Syariah KCP Setiabudi Medan. This study used a quantitative method with a questionnaire research instrument with multiple regression analysis. The sampling method uses total sampling, with a total population of 40 employees at Bank BTN Syariah Kcp Setiabudi and a total sample of 40 employees at Bank BTN Syariah Kcp Setiabudi. The results showed that the effect of significant performance evaluation on the quality of tcount> ttable was 5.652> 1.683 and the resulting significance value was 0.000 <level of significance 0.05. This means that the effect of performance evaluation has a significant effect on frontliner service quality at Bank Btn Syariah Kcp Setiabudi Medan, and the results show that work motivation has a significant effect on service quality tcount > ttable 2.273 > 1.683 and the resulting significance value is 0.016 <significant level of 0.05. This shows that work motivation has a significant effect on the quality of Frontliner services at Bank BTN Syariah KCP Setiabudi Medan.